Pembangunan Hukum yang Mengakomodir Pluralisme di Indonesia - La Ode Angga (UIN Sunan Kalijaga Yogyakarta, 2012)
Pluralism, a popular diversity, is not only an attitude of acknowledging and accepting a reality of pluralistic society, but also a sincere attitude to accept the reality as a positive value, as the grace of God to mankind. Therefore, it will enrich the cultural growth through the dynamic interaction and cross-diverse cultural exchanges. Pluralism is a way to push the nation's cultural enrichment. Indonesian culture or